PENGARUH IDEALISME DAN RELATIVISME TERHADAP SENSITIVITAS ETIKA MAHASISWA BISNIS DI YOGYAKARTA - FRASTO BIYANTO; YUSTI PUJISARI (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
This study aims to examine the relationship between ethical orientation and ethical sensitivity. Ethical orientation variables are divided into 2 parts, namely idealism and relativism. In addition, this study also examines differences in ethical sensitivity, idealism and relativism based on gender (male and female) and college time (junior and senior students).The proposed hypothesis is 3 parts. The first part consists of Ha1a and Ha1b. The results of alternative hypothesis 1a, namely there is a positive influence between idealism orientation on ethical sensitivity. The result of alternative hypothesis 1b is that there is a negative influence between ethical orientation (relativism) on ethical sensitivity.Part 2 hypothesis examines differences in ethical sensitivity, idealism and relativism based on gender. There are 3 alternative hypotheses in part 2 and are tested by ANOVA test. The result is only differences in relativism based on gender that are empirically supported.The third part of the hypothesis examines the differences in ethical sensitivity, idealism and relativism based on differences in college time. There are 3 alternative hypotheses in this 3rd section and are tested by ANOVA test. The results show that there are differences in ethical orientation both in the dimensions of idealism and relativism based on college (senior and junior students)